Adsorption of corrosion inhibitor 1-dodecylpyridinium chloride on carbon steel studied by in situ AFM and electrochemical methods - Pandarinathan, Vedapriya; Lepkova, Katerina; Bailey, Stuart; Becker, Thomas; Gubner, Rolf (American Chemical Society, 2014)
Corrosion rates are influenced by the formation of inhibitor aggregates at the steel surface. In situ atomic force microscopy (AFM) was used to investigate the adsorbed structures of cationic surfactant 1-dodecylpyridinium chloride (DPC) at a carbon steel surface in relation to its performance as a CO2-corrosion inhibitor. An increase in the water contact-angle in the presence of DPC indicated its adsorption at the steel, and in situ AFM visualization confirmed the formation of DPC aggregates. The aggregates changed from hemispherical to cylindrical shape with increasing DPC concentration in CO2-saturated brine, resulting in a decrease in corrosion rates as determined by electrochemical measurements. For comparison to the aggressive CO2 environment, the inhibition behavior of DPC was monitored in less corrosive N2-saturated solutions. Formation of cylindrical aggregates was quicker, and a lower corrosion rate was observed in brine saturated with N2 compared to CO2.